TAFSÎR ON JIHAD VERSES IN AKU MELAWAN TERORIS: Relevance Measurement in The Perspective of Fakhr Dîn al-Râzî - Hamdan, Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
A discourse on justification of radical act faked as jihad based on Fakhr al-DÃ®n al-RÃ¢zÃ®â€™s perspective is the cause of this study. The question is â€œHow is al-RÃ¢zÃ®â€™s opinion on verses used to justify radical acts which are faked as jihad?â€ This study uses the perspective of Fakhr al-DÃ®n al-RÃ¢zÃ®â€™s TafsÃ®r bi al-Raâ€™yi. This is a library research employing qualitative explorative paradigm. All data are in the form of documentation; primary data are from MafÃ¢tÃ®á¸¥ al-Ghayb and book entitled Aku Melawan Teroris as well as other secondary data. The study shows, first: jihad and its meaning are relevant with the period of Quran revelation to date and theologically they will also be relevant in the future; nothing changes from jihadâ€™s concept and substance except the situation and condition. Second, there are five verses in Quran becoming the justification basis of radical acts in the name of jihad i.e. Q.S. al-Tawbah [9]: 5, Q.S. al-Tawbah [9]: 14, QS al-Tawbah [9]: 36, Q.S. AnfÃ¢l [8]: 39, andÂ Q.S. al-Baqarah [2]: 191; yet it is contra productive for al-RÃ¢zÃ®. Through this study, al-RÃ¢zÃ®â€™s tafsÃ®r model is expected to be a formula and new opinion to deeply comprehend, contextual wise, the meaning of those verses.